Neurosteroid and benzodiazepine combination therapy reduces status epilepticus and long‐term effects of whole‐body sarin exposure in rats - Lucille Lumley; Dennis Miller; William T. Muse; Brenda Marrero‐Rosado; Marcio de Araujo Furtado; Michael Stone; Jeffrey McGuire; Christopher Whalley (Epilepsia Open, 2019)
Abstract Objective Our objective was to evaluate the protective efficacy of the neurosteroid pregnanolone (3α‐hydroxy‐5β pregnan‐20‐one), a GABAA receptor‐positive allosteric modulator, as an adjunct to benzodiazepine therapy against the chemical warfare nerve agent (CWNA) sarin (GB), using whole‐body exposure, an operationally relevant route of exposure to volatile GB. Methods Rats implanted with telemetry transmitters for the continuous measurement of cortical electroencephalographic (EEG) activity were exposed for 60 minutes to 3.0 LCt50 of GB via whole‐body exposure. At the onset of toxic signs, rats were administered an intramuscular injection of atropine sulfate (2 mg/kg) and the oxime HI‐6 (93.6 mg/kg) to increase survival rate and, 30 minutes after seizure onset, treated subcutaneously with diazepam (10 mg/kg) and intravenously with pregnanolone (4 mg/kg) or vehicle. Animals were evaluated for GB‐induced status epilepticus (SE), spontaneous recurrent seizures (SRS), impairment in spatial memory acquisition, and brain pathology, and treatment groups were compared. Results Delayed dual therapy with pregnanolone and diazepam reduced time in SE in GB‐exposed rats compared to those treated with delayed diazepam monotherapy. The combination therapy of pregnanolone with diazepam also prevented impairment in the Morris water maze and reduced the neuronal loss and neuronal degeneration, evaluated at one and three months after exposure. Significance Neurosteroid administration as an adjunct to benzodiazepine therapy offers an effective means to treat benzodiazepine‐refractory SE, such as occurs following delayed treatment of GB exposure. This study is the first to present data on the efficacy of delayed pregnanolone and diazepam dual therapy in reducing seizure activity, performance deficits and brain pathology following an operationally relevant route of exposure to GB and supports the use of a neurosteroid as an adjunct to standard anticonvulsant therapy for the treatment of CWNA‐induced SE.